Melatonin Use in Pediatrics: A Clinical Review on Indications, Multisystem Effects, and Toxicity - Pranita Shenoy; Adriana Etcheverry; Jalyn Ia; Manisha Witmans; Mary Anne Tablizo (MDPI AG, 2024)
Exogenous melatonin is typically used for sleep regulation in the context of insomnia either in healthy children or those with neurodevelopmental disabilities. It is also used for the management of circadian rhythm sleep disorders in pediatric and adolescent patients. There are also many other possible indications that we will discuss in this paper beyond the role of melatonin for sleep regulation, including its potential use for various areas of medicine such as inflammatory conditions. Since melatonin is unregulated in the United States, distributed over the counter and perceived to be natural and safe, it has become available in many forms in the last two decades. With increasing sleep disturbances and mental health problems after the COVID-19 pandemic, melatonin has become even more popular and studies have shown a dramatic increase in use as well as resulting side effects, including melatonin overdose. As melatonin is generally viewed by physicians as a benign medication, we hope to increase awareness of melatonin's properties as well as negative side effects to optimize its use in the pediatric population.